New primate genus from the Miocene of Argentina - Tejedor, Marcelo Fabian (2006)
Killikaike blakei is a new genus and species of anthropoid from the late Early Miocene of southeastern Argentina based on the most pristine fossil platyrrhine skull and dentition known so far. It is part of the New World platyrrhine clade (family Cebidae; subfamily Cebinae) including modern squirrel (Saimiri) and capuchin monkeys (Cebus) and their fossil relatives known from Early to Middle Miocene and subrecent periods. Living cebines are relatively largebrained, adroit predatory foragers and live within complex social groups, and wild capuchins exhibit a wide range of behaviors associated with enhanced intelligence. We show that K. blakei lacks diagnostic derived characteristics of the lower face and premolar dentition that are shared by modern cebines, but its strongly vaulted frontal bone and capacious anterior cranial fossa indicate the early evolution of an enlarged forebrain.